Learning and working on an interprofessional training ward in neonatology improves interprofessional competencies - Hannah L. Schwarz; Christine Straub; Sebastian F. N. Bode; Nicole Ferschl; Christian Brickmann; Christian Brickmann; Pascal O. Berberat; Marcus Krüger (Frontiers in Medicine)
IntroductionInterprofessional education (IPE) is essential for healthcare professionals to prepare them for future interprofessional collaboration (IPC). Interprofessional training wards (ITWs) have been set up for IPE and results have been published. There are no published studies on ITWs in neonatology. We have designed and established the Interprofessional Training Ward in Neonatology (IPANEO) for nursing trainees (NT) and medical students (MS) in a neonatological intermediate care (IMC) ward. We report on the concept and the results with regard to the interprofessional competencies of the participants, including parent satisfaction.MethodsSupervision by medical and nursing learning facilitators, 2week blocks each with 2 NT (n = 30) and 2 MS (n = 23) in their final year, ward-in-ward concept, 3 patients cared for. Evaluation of the participants (pre/post) with the Interprofessional Socialisation and Valuing Scale (ISVS), the Interprofessional Collaboration Scale (ICS) with questions on IP communication, accommodation and isolation as well as with an IPANEO-specific evaluation (IPQ), an external evaluation with the “Observational Questionnaire for Learning Facilitators” (OQLF) and a “Questionnaire on Parent Satisfaction” (PSQ) (n = 33).ResultsIPANEO participants showed significant increases in competencies in IP communication, accomodation and isolation (ICS), a better IP-collaboration and a higher role definition (IPANEO specific questionnaire). The ISVS 9A/B global scores increased. According to the self-assessment there were significant improvements in the external evaluation in all IP-categories (OQLF). The feedback from the parents was significantly positive (PSQ).ConclusionInterprofessional learning and working on IPANEO had a positive impact on interprofessional competencies with high parent satisfaction.